Determinants of job hopping factors among lecturers in private universities, Malaysia - SELVANATHAN, M; BUGA, M.M; SUPRAMANIAM, M; ARUMUGAM, TH; JAYABALAN, N (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTJob-hopping is becoming a phenomenon over the years as lecturers keep moving from one job to another for better opportunities and self-development. The objective of this research is to study the factors that influence job-hopping in Private University in Malaysia. The anteceding factors are lack of promotion and growth, salary and benefits issues, job insecurities and work-life imbalance. A total of 120 questionnaires were distributed to participants who work in private university, Malaysia. The results reported that salary and benefits issues, job insecurities and work-life imbalance have a significant and positive correlation with job-hopping. RESUMENEl cambio de trabajo se está convirtiendo en un fenómeno a lo largo de los años a medida que los profesores se mueven de un trabajo a otro. El objetivo del estudio es analizar los factores que promueven el cambio de trabajo como son la falta de promoción y crecimiento, el salario y los problemas de beneficios. Se distribuyeron un total de 120 cuestionarios a los participantes que trabajan en una universidad privada, Malasia. Los resultados informaron que los problemas salariales y de beneficios, las inseguridades laborales y el desequilibrio entre la vida laboral y personal tienen una correlación significativa y positiva con la inestabilidad laboral.